Expanding frontiers in materials chemistry and physics with multiple anions. Issue 1 (December 2018) - Kageyama, Hiroshi; Hayashi, Katsuro; Maeda, Kazuhiko; Attfield, J.; Hiroi, Zenji; Rondinelli, James; Poeppelmeier, Kenneth
Abstract During the last century, inorganic oxide compounds laid foundations for materials synthesis, characterization, and technology translation by adding new functions into devices previously dominated by main-group element semiconductor compounds. Today, compounds with multiple anions beyond the single-oxide ion, such as oxyhalides and oxyhydrides, offer a new materials platform from which superior functionality may arise. Here we review the recent progress, status, and future prospects and challenges facing the development and deployment of mixed-anion compounds, focusing mainly on oxide-derived materials. We devote attention to the crucial roles that multiple anions play during synthesis, characterization, and in the physical properties of these materials. We discuss the opportunities enabled by recent advances in synthetic approaches for design of both local and overall structure, state-of-the-art characterization techniques to distinguish unique structural and chemical states, and chemical/physical properties emerging from the synergy of multiple anions for catalysis, energy conversion, and electronic materials. Inorganic compounds with multiple anions have added a new dimension to the discovery of materials. Here the authors review the recent progress in the development of mixed-anion compounds, focusing on the roles of multiple anions in synthesis, characterization and properties.